State-to-state dynamics of the C+(2P) + SH(X2Π) → H(2S) + CS+(X2Σ+) reaction using a time-dependent wave packet and quasi-classical trajectory methods - Liu, Dong; Zhao, Juan; Wang, Wei; Song, Yuzhi; Meng, Qingtian; Zhang, Lulu (Frontiers in Physics, 2022)
The time-dependent quantum wave packet (TDWP) and quasiclassical trajectory (QCT) are the basic research methods of reaction dynamics. Utilizing these two methods, the total reaction probability (J = 0), integral cross section (ICS) and rate parameter for the C+(2P) + SH(X2Π)(v=0, 1, 2, 3) → H(2S) + CS+(X2Σ+) reactions are calculated on an accurate potential energy surface [Zhang et al. Phys. Chem. Chem. Phys. 2022, 24, 1007]. The results of QCT are slightly different from those of TDWP in value, but the trend is consistent. They are also weakly dependent on the initial vibrational excitation of SH. The state-to-state reaction probability and ICS at fixed collision energies (0.1, 0.3, 0.5 and 0.7 eV) are first calculated using QCT methods. It is hoped that our work can arouse experimentalists to study the dynamics of this interesting but rarely discussed system.